2016
DOI: 10.1111/jbi.12791
|View full text |Cite
|
Sign up to set email alerts
|

Present and past climatic effects on the current distribution and genetic diversity of the Iberian spadefoot toad (Pelobates cultripes): an integrative approach

Abstract: Aim Predicting species responses to global change is one of the most pressing issues in conservation biogeography. A key part of the problem is understanding how organisms have reacted to climatic changes in the past. Here, we use species distribution modelling to infer the effects of climate changes since the Last Interglacial (LIG, c. 130,000 yr bp) on patterns of genetic structure and diversity in the western spadefoot toad (Pelobates cultripes) in combination with spatially explicit phylogeographical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 99 publications
7
45
1
Order By: Relevance
“…The strong barrier effect exerted by Sierra de Guadarrama on P. cultripes is well supported based on high overall population differentiation (Table S1.4) and results of the clustering and causal modelling approaches (Table , Figures and S2.9–S2.11). This barrier effect is consistent with the absence or rarity of this species above 1,500 m (Cejudo, ) and the strong phylogeographical break at the Central System (Gutiérrez‐Rodríguez, Barbosa, et al., ). Mountain passes in Sierra de Guadarrama are above the higher reported altitudes for this species except at Somosierra and Alto del León (Figure ).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The strong barrier effect exerted by Sierra de Guadarrama on P. cultripes is well supported based on high overall population differentiation (Table S1.4) and results of the clustering and causal modelling approaches (Table , Figures and S2.9–S2.11). This barrier effect is consistent with the absence or rarity of this species above 1,500 m (Cejudo, ) and the strong phylogeographical break at the Central System (Gutiérrez‐Rodríguez, Barbosa, et al., ). Mountain passes in Sierra de Guadarrama are above the higher reported altitudes for this species except at Somosierra and Alto del León (Figure ).…”
Section: Discussionsupporting
confidence: 82%
“…If this effect is significant in the present interglacial period, it is safe to assume that it was probably stronger during the Pleistocene, when glaciers covered large areas in Sierra de Guadarrama (Domínguez‐Villar et al., ). This long‐term effect could explain the phylogeographical breaks found in P. cultripes (Gutiérrez‐Rodríguez, Barbosa, et al., ) and H. molleri (Sánchez‐Montes & Martínez‐Solano, unpublished), two species showing a clear north–south subdivision in the Iberian Peninsula and meeting at the Central System mountains.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Restrictions to population connectivity imposed by elevation and slope probably operate on deeper timescales than those related to land use/cover. Recent phylogeographic studies have shown that the Iberian Central System has acted as an historical barrier to gene flow in the two species, separating different evolutionary groups north and south of this mountain range (Gutiérrez‐Rodríguez, Barbosa, & Martínez‐Solano, ,b). These groups would have experienced limited connectivity during the Last Glacial Maximum (21 ka), as glacial areas occupied lower altitudes around 1,350 m in the study area (Bullón, ).…”
Section: Discussionmentioning
confidence: 99%
“…Their Quaternary changes and climatic favorability have recently been analyzed, particularly for Pelobates cultripes (Lobo et al 2016;Gutiérrez-Rodríguez et al 2017). …”
Section: Amphibiansmentioning
confidence: 99%